Límites a la autonomía territorial de los municipios frente a la prohibición de exclusión de zonas de explotación minera en el ejercicio de la planificación y el ordenamiento territorial (2016)
In Colombia, exploitation and mining exploration exercise is an activity of general interest that is ruled by series of administrative procedures which affect the territorial development, concerning the planning of social, environmental and cultural municipalities, these do not have a real space of participation and advocacy when somebody (person or institution) would have a license of exploitation or mining exploration when there are excluded zones to do it. Despite the fact that institutions such as the Constitutional Court have made the attempt to find a balance between the principles of the unitary Republic and Territorial autonomy, the exercise of the functions conferred of the towns as territorial entities for their own management and their own interests, they are still being limited and sometimes almost ignored when it involves the State in the development of competences that have to do with these issues of national interest.